2003
DOI: 10.1109/tpwrs.2002.807076
|View full text |Cite
|
Sign up to set email alerts
|

Solving the revenue reconciliation problem of distribution network providers using long-term marginal prices

Abstract: In this paper, we describe an integrated methodology to compute long-term marginal prices in distribution networks. Long-term marginal prices are considered the most interesting and economically sound way of allocating network costs to users. Additionally, they inherently deal with the revenue reconciliation problem, as they generally do not require other large supplementary tariff terms. The proposed methodology uses fuzzy sets to model uncertainties in load forecasts and considers several criteria to guide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The fundamental issue is whether DG promoters must pay by the use of the network these additional investment charges or receive any compensation due to the avoided or deferral investments produced by their placement into the network. Some approaches have been introduced to deal with this problem using long term marginal pricing [4]. Some methods are proposed in a nodal level and obtained as a product of an optimal expansion plan study with hard computational efforts [5].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental issue is whether DG promoters must pay by the use of the network these additional investment charges or receive any compensation due to the avoided or deferral investments produced by their placement into the network. Some approaches have been introduced to deal with this problem using long term marginal pricing [4]. Some methods are proposed in a nodal level and obtained as a product of an optimal expansion plan study with hard computational efforts [5].…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the revenues and outlays would define the grid payment. The practical application of this methodology to transmission grids showed that cost recovery was normally under 25% [11,12]. Hence, much higher additional costs would have to be charged, distorting the STMC message completely.…”
Section: Methodologies For Allocating Distribution Costsmentioning
confidence: 99%
“…Another LTIC-based proposal for distribution grids was put forward in [18]. Here also, calculations were performed with a long-term planning model, based on operating costs, reliability (power not supplied) and investment.…”
Section: Ltmc-based Distribution Pricingmentioning
confidence: 99%
“…In turn, little to no recovery of the total cost of service provision is signaled at present, which in turn provides very little incentive for future demand-side developments (Reneses and Rodríguez, 2014). Reneses and Rodríguez (2014) point to an application in P erez- Arriaga et al (1995) and Ponce de Leão and Saraiva (2003) where cost recovery is below 25 percent for transmission and estimated to be even lower at the distribution level. Full cost recovery requires the addition of extra costs, which in turn distorts the message that short-run marginal pricing is meant to send.…”
Section: Underlying Theory Of Network Pricingmentioning
confidence: 99%